Is Football or Badminton Associated With More Positive Affect? The Links Between Affects and Sports Club Membership Among French Adolescents - Barbry, Alexis; Carton, Annie; Coquart, Jérémy; Ovigneur, Hervé; Amoura, Camille; Nuytens, Williams; Orosz, Gabor (Frontiers in Psychology, 2021)
Prior studies extensively examined the way sports club membership can lead to beneficial affective outcomes. Prior experiments also found that team sports, intensive sports, and sports that are frequently pursued can lead to even more affective benefits. However, no prior studies examined the differences between the affective benefits of specific sports. Based on prior results, we supposed that certain sports that meet all the previously set criteria—will provide the greatest affective benefits. The present large-scale investigation examined the data of adolescents (N=12,849, female=5,812, aged between 10 and18, Mage=12.56 years, SDage=2.00) and aimed to fill this gap. Firstly, the results showed that—although differences in affect can be found between the lack of club membership and most of the sports club memberships—the differences between the specific sports are less striking. Secondly, the sports that are associated with the highest level of positive and the lowest level of negative affectivity are not necessarily the ones expected. Finally, adolescents who practice athletics, reported the lowest means of negative, and the highest means of positive affect. However, it did not differ significantly from the results regarding the most practiced sport in France: soccer. Our results suggest that, soccer as the most practice sport among French adolescents, was associated with more positive affects than the majority of the 10 most licensed members French sports practiced by teens between 2008 and 2019. All in all, being a member of a sports club is associated with affective benefits, and some specific sports clubs can have some extra benefits.